2015
DOI: 10.1039/c4cc10113h
|View full text |Cite
|
Sign up to set email alerts
|

Ring-opening copolymerization (ROCOP): synthesis and properties of polyesters and polycarbonates

Abstract: Controlled routes to prepare polyesters and polycarbonates are of interest due to the widespread application of these materials and the opportunities provided to prepare new copolymers. Furthermore, ring-opening copolymerization may enable new poly(ester-carbonate) materials to be prepared which are inaccessible using alternative polymerizations. This review highlights recent advances in the ring-opening copolymerization catalysis, using epoxides coupled with anhydrides or CO2, to produce polyesters and polyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
431
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 501 publications
(451 citation statements)
references
References 235 publications
3
431
1
4
Order By: Relevance
“…In contrast, Arai et al found that the addition of carbon dioxide to the first reaction step results in improved yield both SO and SC [11]. A low yield of styrene carbonate was obtained possibly due to the fact that the epoxidation of styrene in the presence of CO 2 could allow the formation of the linear oligomers and polycarbonates, which in turn could impede the subsequent reaction of carbon dioxide with in situ formed epoxide [22,23]. Therefore, in the next experiment, CO 2 was added to the reactor in the second step of the process.…”
Section: The Impact Of the Order Of Reagent Introductionmentioning
confidence: 91%
“…In contrast, Arai et al found that the addition of carbon dioxide to the first reaction step results in improved yield both SO and SC [11]. A low yield of styrene carbonate was obtained possibly due to the fact that the epoxidation of styrene in the presence of CO 2 could allow the formation of the linear oligomers and polycarbonates, which in turn could impede the subsequent reaction of carbon dioxide with in situ formed epoxide [22,23]. Therefore, in the next experiment, CO 2 was added to the reactor in the second step of the process.…”
Section: The Impact Of the Order Of Reagent Introductionmentioning
confidence: 91%
“…The chemical fixation and conversion of carbon dioxide into valuable chemicals is generally regarded as an excellent method from both the environmental protection and resource utilization standpoints [1,2,3,4,5]. As a naturally abundant, cheap, recyclable, and nontoxic carbon source, carbon dioxide has been involved in various organic reactions, especially the cycloaddition of epoxides with carbon dioxide to produce carbonates [6,7,8,9,10,11]. This reaction is a standard “atom-economy” and “green-chemistry” reaction to produce environmentally-friendly propylene carbonate that is widely utilized as a special solvent in many chemical industries such as liquefied natural gas (LNG), the textile printing industry, lithium batteries, and wood processing [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the widespread concern on the coupling of epoxide and CO 2 to from polyester [1] with good biodegradability and biocompatibility, the alternative approach [2] from the ring-opening copolymerization of epoxide with anhydride is not popular enough probably due to a missing gag on the greenhouse gas consumption. Nonetheless, the availability of structurally diverse anhydrides enables a wider variety of polymeric backbones for the obtained polyesters with potential applications in commodity materials [3] and biological materials [4].…”
mentioning
confidence: 98%